Edukasi Pencegahan TBC Berbasis Kreativitas Dan Inovasi Siswa di SMP Negeri 5 Cilacap - Nurfauzi, Yuhansyah; Farabi, Meka Faizal; Ginanjar Triyono, Heru; Raafi R, Muhammad; Iskandar, Drajat (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
Tuberculosis (TB) remains one of the major health issues in Cilacap Regency. Preventive efforts can be initiated early through educational approaches combined with creativity and innovation. This community service program was carried out at SMP Negeri 5 Cilacap by empowering students through the Youth Scientific Research (KIR) group. The aim was to improve students’ understanding of TB prevention while fostering their creativity in producing health-based scientific works. The activities included: (1) presentations on TB, innovation, and the importance of creative products for health; (2) counseling on affordable functional food based on soybeans delivered by an immunology lecturer; (3) education on TB prevention, transmission, and stigma reduction provided by a community nursing lecturer; and (4) training on developing scientific works and innovative products, such as tempe-based biscuits as a high-protein source. Pretest results showed that only 30% of students understood the material, while 70% did not. After the program, understanding significantly increased to 85% of students, with only 15% remaining less informed. These findings indicate that creativity- and innovation-based education is effective in enhancing students’ knowledge of TB prevention.